2015
DOI: 10.1016/j.mayocp.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The Childhood Obesity Epidemic as a Result of Nongenetic Evolution: The Maternal Resources Hypothesis

Abstract: Over the past century, socio-environmental evolution (e.g., reduced pathogenic load, decreased physical activity [PA], improved nutrition) led to cumulative increments in maternal energy resources (i.e., body mass, adiposity) and decrements in energy expenditure and metabolic control. These decrements reduced the competition between maternal and fetal energy demands and increased the availability of energy substrates to the intrauterine milieu. This perturbation of mother-conceptus energy partitioning stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
99
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(106 citation statements)
references
References 165 publications
(198 reference statements)
3
99
0
1
Order By: Relevance
“…We [60] and many others [61] have shown the importance of maternal BMI in predicting later health problems in the offspring and there is growing interest in optimising maternal health to improve on childhood obesity outcomes. Most recently, this has elegantly been put forward as the 'Maternal Resources Hypothesis' which posits that the childhood obesity epidemic is the result of the evolutionary processes of maternal effects, phenotypic evolution and socio-environmental evolution, leading to a tipping point in human energy metabolism at which adipocytes outcompete other cell types in the acquisition and sequestering of nutrient energy [62].…”
Section: Novel Approaches At Preventionmentioning
confidence: 99%
“…We [60] and many others [61] have shown the importance of maternal BMI in predicting later health problems in the offspring and there is growing interest in optimising maternal health to improve on childhood obesity outcomes. Most recently, this has elegantly been put forward as the 'Maternal Resources Hypothesis' which posits that the childhood obesity epidemic is the result of the evolutionary processes of maternal effects, phenotypic evolution and socio-environmental evolution, leading to a tipping point in human energy metabolism at which adipocytes outcompete other cell types in the acquisition and sequestering of nutrient energy [62].…”
Section: Novel Approaches At Preventionmentioning
confidence: 99%
“…[1][2][3]17 We have previously reported that a progressive decline in PA, especially in occupational and household PA, over the past 5 decades is a primary cause of the obesity epidemic that has been spreading in our society, and this also impacts the health of the next generation and contributes to many chronic diseases and adverse CVD outcomes. [18][19][20][21] Considerable evidence suggests that high levels of PA and ET are associated with improved clinical outcomes, beyond those expected on the basis of effects on traditional risk factors for CVD, suggesting that other factors (eg, autonomic function, preconditioning, and endothelial function) might also explain the marked benefits noted. [1][2][3]5 This evidence comes from studies evaluating the effects of both leisure time PA and occupational PA on subsequent prognosis.…”
mentioning
confidence: 99%
“…It is well known that the prenatal period is crucial in the establishment of the epigenome (21,(56)(57)(58). One of the most critical processes during pregnancy is the establishment of imprinted genes.…”
Section: Evidence Of Prenatal Epigenetic Influencesmentioning
confidence: 99%